2019
DOI: 10.1186/s13018-019-1117-x
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory consequences of limb ischemia/reperfusion in ovariectomized rats treated with zoledronic acid

Abstract: Background Nitrogen-containing bisphosphonates (BIS) are potent therapeutics in osteoporosis, but their use may result in osteonecrotic side-effects in the maxillofacial region. Periosteal microcirculatory reactions may contribute to the development of bone-healing complications, particularly in osteoporotic bones, where ischemia–reperfusion (IR) events often develop during orthopaedic/trauma interventions. The effect of BIS on the inflammatory reactions of appendicular long bones has not yet been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Periosteal activity is believed to be of crucial importance in bone physiology and pathophysiology, and therefore, in the healing process [ 13 ]. A basic requirement for the preservation of periosteal function is the presence of adequate blood flow in periosteal vessels, because normal healing seems to be critically linked to the reestablishment of periosteal microcirculation [ 14 , 15 ]. Bisphosphonates are known to affect periosteal perfusion by inducing leukocyte-endothelial cell interactions [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periosteal activity is believed to be of crucial importance in bone physiology and pathophysiology, and therefore, in the healing process [ 13 ]. A basic requirement for the preservation of periosteal function is the presence of adequate blood flow in periosteal vessels, because normal healing seems to be critically linked to the reestablishment of periosteal microcirculation [ 14 , 15 ]. Bisphosphonates are known to affect periosteal perfusion by inducing leukocyte-endothelial cell interactions [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A basic requirement for the preservation of periosteal function is the presence of adequate blood flow in periosteal vessels, because normal healing seems to be critically linked to the reestablishment of periosteal microcirculation [ 14 , 15 ]. Bisphosphonates are known to affect periosteal perfusion by inducing leukocyte-endothelial cell interactions [ 15 , 16 ]. A previous study demonstrated an increased number of adherent and rolling leukocytes in the postcapillary venules of the mandibular periosteum of bisphosphonate-treated mice compared with that in non-treated animals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%